Genetic Diversity of Dahongjun The Commercially Important 'Big Red Mushroom" From Southern China - Li, Mochan (My University, 2009)
The genus Russula is among the most numerous and complex mushroom genera. They form symbiotic associations with a variety of plants such as pines, oaks, spruce, and birches and play vital roles in forest ecosystem. Species in this genus are widely distributed throughout the world, from the tropics to subtropics, temperate regions, and the arctic zone. Intensive studies on this genus have been carried out on European and North American Russula. However, there are very few studies on Asian Russula.
In southwestern China the favorable climate stimulates the production of a large population of Russula. A wild mushroom commonly called "dahongjun" or the "big red mushroom" by the locals, has been harvested, consumed and/or exported as an exotic food for many years. Although ecologically and economically important, very little is known about this mushroom, including its basic ecology and population genetic structure. In this study, we investigated the genetic diversity and geographic structure of dahongjun using sequences of the internal transcribed spacer (ITS) regions of the ribosomal RNA gene cluster. We found that this exotic mushroom contained at least three divergent lineages, with one corresponding to the recently described Russula griseocarnosa and two others likely representing closely related novel species within the genus Russula. Both phylogenetic and population genetic analyses suggested that dahongjun populations were geographically structured and gene flow among regions were limited. We also estimated the size of the genets for one Russula lineage by comparing haplotypes derived from four different DNA markers. Small genets suggest that sexual reproduction is likely more dominant than clonal reproduction in dahongjing. We found that the size of dahongjun genets ranged from 30cm to less than 3m, and widespread recombination within a local population. This result was consistent with the findings from other Russula species. Our study provided the first insights into the diversity and population biology of this endemic gourmet mushroom in southern China. This work serves as a great referencing resource on conducing conservation practices for wild Russula.
Keywords: Biology; Biology